ALPHA-GLUCOSIDASE INHIBITOR ACTIVITIES AND PHYTOCHEMICALS SCREENING OF THE PEPEROMIA GENUS CULTIVATED IN INDONESIA - SAEPUDIN, SYUMILLAH; SUSILAWATI, YASMIWAR (International Journal of Applied Pharmaceutics, 2022)
Objective: Peperomia is a genus belong to Piperaceae family, which is valuable as ornamental and has several medical uses but not widely explored in their pharmacological activities. Some peperomia plant has been investigated and reported to have various activities, recently as diabetes mellitus. This research was conducted to screening phytochemical profile and to determine alpha-glucosidase inhibitor activities of five species in genus Peperomia that are easy to grow and has been cultivated in Indonesia. Methods: Dried leaves were macerated with 70% ethanol and vaporized by rotary evaporator. Phytochemical screening was conducted using qualitative chemical analysis and inhibition of alpha-glucosidase was conducted using p-nitrophenyl-α-D-glucopyranoside as substrate, and absorbance was measured with a spectrophotometer UV-Vis. Results: The phytochemical screening of the leaves extracts demonstrated the presence of various secondary metabolites, such as flavonoids, phenol, tannins, quinone, alkaloids, saponins, steroids, and triterpenoids. The inhibition of alpha-glucosidase showed that the IC50 value of ethanol extract of P. obtusifolia, P. clusiifolia, P. caperata (green), P. caperata (red), and P. argyreia leaves were 2.90; 18.05; 21.46; 23.81; and 48.70 µg/ml respectively. Conclusion: The highest inhibition of alpha-glucosidase activity was showed by P. obtusifolia with an IC50 value of 2.90 µg/ml. Further research is needed to explore its potential as an antidiabetic.